Subcortical connections to human amygdala and changes following destruction of the visual cortex - Tamietto, M; Pullens, P; De Gelder, B; De Gelder, B; Weiskrantz, L; Goebel, R; Goebel, R (2012)
Nonconscious [1-6], rapid [7, 8], or coarse [9] visual processing of emotional stimuli induces functional activity in a subcortical pathway to the amygdala involving the superior colliculus and pulvinar. Despite evidence in lower mammals [10, 11] and nonhuman primates [12], it remains speculative whether anatomical connections between these structures exist in the human brain [13-15]. It is also unknown whether destruction of the visual cortex, which provides a major input to the amygdala, induces modifications in anatomical connections along this subcortical pathway. We used diffusion tensor imaging to investigate in vivo anatomical connections between human amygdala and subcortical visual structures in ten age-matched controls and in one patient with early unilateral destruction of the visual cortex. We found fiber connections between pulvinar and amygdala and also between superior colliculus and amygdala via the pulvinar in the controls as well as in the patient. Destruction of the visual cortex led to qualitative and quantitative modifications along the pathways connecting these three structures and the changes were confined to the patient's damaged hemisphere. The present findings thus show extensive neural plasticity in the anatomical connections between subcortical visual structures of old evolutionary origin involved in the processing of emotional stimuli. © 2012 Elsevier Ltd.